ИНГЛИЗ ВА ЎЗБЕК АДАБИЙ АЛОҚАЛАРИ - Ўринова , Дилдора Бекмахматовна (Educational Research in Universal Sciences, 2023)
This article discusses issues related to the English-Uzbek relations, its importance in the development of science, culture, and economy